Storage Optimization at PT XY Using Class Based Storage and FSN Analysis Methods - Septian Aditya; Said Salim Dahda (Universitas Islam Raden Rahmat, Malang, 2025)
This research aims to make the process of picking goods according to their type easier, so that the distance of transporting materials is shorter than the previous distance. FSN Analysis classifies goods based on the frequency of demand, and Class Based Storage groups goods based on their category (FSN) and places them in strategic locations in the warehouse. In this research, changes to the warehouse layout were made manually based on the results of the FSN analysis and the application of the Class Based Storage method. The results of the FSN Analysis are 7 types of Fast moving category goods, 6 types of Slow moving category goods, and 2 types of Non-moving category goods. FSN analysis is made by sorting all frequencies of goods from the highest value, as well as cumulative calculations and frequency percentages. By comparing the initial layout with the proposed layout, data processing results in a total decrease from IDR 6.558.992,00/ month to IDR 3.825.480,00/ month, or 41,7% more efficient by using the proposed layout based on the Class Based Storage method and FSN Analysis reduce moment material handling 42%. Therefore, it can be concluded that the problem of storing goods in PT XY's warehouse will be solved if using a storage optimization policy that uses the Class Based Storage method and FSN Analysis as a review and reference material in arranging future storage layouts.